Advances in research project IBUMECO2: project and process description, methodology, and goals expected. Issue 2 (26th September 2022) - Gallego Fernández, Luz M.; Estévez, Esmeralda Portillo; Baena‐Moreno, Francisco M.; Vilches Arena, Luis F.; Rubia, Benito Navarrete
Abstract: In this work, the research project IBUMECO2 is presented for the first time. This project rises as a need to implement negative emissions technologies and circular economy approaches in our current energy production system. The overall goal of the project is the integration of CO2 capture and utilization in biogas upgrading plants in combination with membrane technology for solvent regeneration. The integration of CO2 capture and utilization in biogas upgrading plants is pivotal for two main reasons: (1) it allows to obtain biomethane, a potential substitute of natural gas; (2) the utilization of the CO2 contained in biogas makes the idea a negative emission technology. The implementation of membrane technology for solvent regeneration makes the process affordable and includes it in a circular economy framework. In this paper, the project and the process are deeply described, including potential technological improvements identified by a state‐of‐the‐art, the methodology and goals expected. © 2022 Society of Chemical Industry and John Wiley & Sons, Ltd.